Black porcelain solar plate and its thermal performance. Issue 6 (1st May 2019) - Xiu, Dapeng; Zhao, Guochen; Zhou, Jixue; Zhang, Suqing
Abstract: In this study, a new percentage named "A value" was proposed, which was the key to evaluate whether solar thermal systems could be put into massive industrial application. A novel type of solar energy collector—black porcelain solar plate was developed. The solar absorptance of black coating was as high as 0.95 and did not decay against time. The performance of black porcelain solar roof systems (BPRSs) was investigated, which could be integrated with buildings and had the A value 2.49‐2.67 times higher than traditional solar thermal systems. The experimental results showed that the thermal efficiencies of BPRSs were more than 50%, which was about 20% higher than traditional solar thermal systems. BPRSs were widely known as low cost, long lifetime, no corrosion, and no aging. They could provide many applications for civil buildings, such as hot water of four seasons, summer air conditioning and winter heating. Once applied widely, solar energy collected by black porcelain solar plates might prospectively be the major source of human energy demand.